The Wire - Die komplette erste Staffel Episode 1-13 - Johnson, Clark; Medak, Peter; Virgo, Clement; Briesewitz, Uta; West, Dominic; Doman, John; Elba, Idris
In chronicling a multi-generational family business dealing illegal drugs and the efforts of the Baltimore police to curb their trade, this series draws parallels between these organizations and the men and women on either side of the battle ... Season One centers around a family of drug dealers and the innerworkings of their empire. It also follows the detectives who are trying to catch the high members of the empire. [www.tv.com]